Seafloor Observation Scenario Exploration Tool: enabling representative exploration of the global deep seafloor - Johannes, Kristen N.; Kennedy, Brian R. C.; Bell, Katherine L. C. (Frontiers in Marine Science, 2023)
Visual observation of the seafloor is invaluable in understanding deep-sea biogeography, uncovering and expanding key global geological, oceanographic, and climate processes. And yet, due to the expense, inefficiency, and inequitable distribution of deep-sea tools, we have barely explored a small, biased fraction of it. Systematic and efficient exploration of the entire deep sea will require a concerted global effort. The current study uses global-coverage geospatial data to develop an interactive online tool for deep seafloor observation planning (i.e., depths below 200 m). The Seafloor Observation Scenario Exploration Tool integrates stakeholder goals and constraints into a dynamic modeling process that combines information about seafloor depth, seafloor geomorphology features, sites of past seafloor observation, Exclusive Economic Zones, and vessel traffic density. With the tool, users can identify maximally suitable areas for seafloor observation, which we envision supporting seafloor expedition planning and marine conservation action.